2011
DOI: 10.1074/jbc.m110.175703
|View full text |Cite
|
Sign up to set email alerts
|

Triacylglycerol Accumulation Activates the Mitochondrial Apoptosis Pathway in Macrophages

Abstract: Programmed cell death of lipid-laden macrophages is a prominent feature of atherosclerotic lesions and mostly ascribed to accumulation of excess intracellular cholesterol. The present in vitro study investigated whether intracellular triacylglycerol (TG) accumulation could activate a similar apoptotic response in macrophages. To address this question, we utilized peritoneal macrophages isolated from mice lacking adipose triglyceride lipase (ATGL), the major enzyme responsible for TG hydrolysis in multiple tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 42 publications
7
78
2
2
Order By: Relevance
“…1). In support of our findings, previous reports have shown that TG stimulates the apoptotic pathway in macrophages (26) and that upregulation of Bcl-2 protects macrophages from apoptosis (27). Taken together, these data strongly suggest that the decrease in macrophage viability after TG treatment was due to activation of the apoptotic pathway.…”
Section: Tg Downregulates Il-1β Expressionsupporting
confidence: 81%
“…1). In support of our findings, previous reports have shown that TG stimulates the apoptotic pathway in macrophages (26) and that upregulation of Bcl-2 protects macrophages from apoptosis (27). Taken together, these data strongly suggest that the decrease in macrophage viability after TG treatment was due to activation of the apoptotic pathway.…”
Section: Tg Downregulates Il-1β Expressionsupporting
confidence: 81%
“…Recently, it has been reported that TG-triggered macrophage cell death is also mediated via a caspase-3/7-dependent apoptotic pathway. 28) It was also reported that caspase-1 is involved in the mitochondrial apoptotic pathway due to activation of caspase-9 and caspase-3. 26) Taken together with our results, we suggest that TG-induced macrophage death is mediated by activation of both the caspase-1-dependent pyroptotic pathway and the caspase-3/7-dependent apoptotic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vivo study, Aflaki et al disclosed a particular pathway related to intracellular triglyceride accumulation that promoted mitochondrial dysfunction with the consequence of programmed cell death in macrophages 19) . Aronis et al stated that exposure to TG provoked down-regulation in mtDNA genomic biogenesis, including Peroxisome proliferator-activated receptor-gamma coactivator-1alpha and nuclear respiratory factor -1, two critical transcription factors to maintain the required mtDNA content 20) .…”
Section: Discussionmentioning
confidence: 99%